Utilization of market waste as organic fertilizer for the people of Hinekombe Village, Jayapura Regency - Suyatno Suyatno; Bambang Suhartawan; Syamsudin Usman; Helen Riupassa; Susi Marianingsih; Hendry Y. Nanlohy (Community Empowerment, 2023)
Pharaa Market is the main market in Hinekombe Village, Sentani District, Jayapura Regency. High market activity has a direct impact on the production of quite a lot of waste, and if it is not handled well, it has the potential to make Pharaa Market a dirty place and reduce consumers' interest in shopping. This will hinder the circulation of the economy and people's income. Therefore, the aim of this community service activity is to increase the village community's understanding and skills in utilizing waste to create organic fertilizer. The methods used are socialization and training. The results obtained indicate that the community has gained a new perspective on the potential of waste and has developed excellent skills in managing waste to produce organic fertilizer.